2021
DOI: 10.3390/ijerph18041638
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Antigen-Based Rapid Diagnostic Testing for Estimating the Coronavirus Disease 2019 Prevalence from the Perspective of the Workers’ Vulnerability before and during the Lockdown

Abstract: Background: No previous study has investigated the SARS-CoV-2 prevalence and the changes in the proportion of positive results due to lockdown measures from the angle of workers’ vulnerability to coronavirus in Greece. Two community-based programs were implemented to evaluate the SARS-CoV-2 prevalence and investigate if the prevalence changes were significant across various occupations before and one month after lockdown. Methods: Following consent, sociodemographic, clinical, and job-related information were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
(30 reference statements)
0
13
0
Order By: Relevance
“…During the first wave of the pandemic, Greece implemented very harsh preventive measures to delay the virus spread. From 10 March to 4 May, wide strict restrictions on public movements were announced, and essential stores, restaurants, and bars were restricted to takeaway service only, thus achieving a low COVID-19 disease burden [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the first wave of the pandemic, Greece implemented very harsh preventive measures to delay the virus spread. From 10 March to 4 May, wide strict restrictions on public movements were announced, and essential stores, restaurants, and bars were restricted to takeaway service only, thus achieving a low COVID-19 disease burden [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, it could spread rapidly in humans as there was no existing immunity [9]. The study of such communities may lead an observer to identify the history and potential modes of transmission and effectively evaluate the impact of infection control strategies [4,9]. In other words, the occurrence of an epidemic in a semi-closed community offers the opportunity for a thorough investigation and is, therefore, of more than usual interest [9].…”
Section: Introductionmentioning
confidence: 99%
“…Four surveillance studies were conducted in Greece, Switzerland, USA, and the Netherlands, which used Ag-RDTs to monitor COVID-19 across an entire town, primary and secondary schoolchildren and teachers, university students and staff, and in professional football clubs, respectively. [41][42][43][44] Sample type Sample type was reported in all but six studies (Supplementary Table 4). Nasal or nasopharyngeal swabs were used in a vast majority of studies that reported sample type, either alone or in combination with another sample type (30/33 studies).…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…This is to a degree moderated by the requirement for international travel (11)(12)(13), which is very strict and may elicit the need for multiple tests and strict adherence to personal protective equipment and epidemiological measures. Regardless of the modes of use, antigen testing is now established as a useful tool in diagnostic capabilities (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%